1978
DOI: 10.1111/j.1365-2125.1978.tb00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine sensitivity in hyperthyroidism and hypothyroidism.

Abstract: 1. Catecholamine sensitivity in hyper‐ and hypothyroidism has been studied using a standardised isoprenaline sensitivity test. 2. Seven patients with hyperthyroidism and seven with hypothyroidism were tested both when showing evidence of thyroid dysfunction and again when euthyroid. 3. No significant differences were seen in heart rate responses to isoprenaline when patients became euthyroid compared to their response when either hyperthyroid or hypothyroid. 4. These results indicate that sensitivity to catech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Many of the clinical manifestations of this disease resemble the effects of stimulation of the sympathetic nervous system, but the reasons for this have never been satisfactorily explained. Increased sensitivity to catecholamines has been said to occur in hyperthyroidism, but catecholamine concentrationresponse curves have not been found to alter in patients when they were hyperthyroid compared to when they were euthyroid (Aoki, Wilson & Theilin, 1972;McDevitt, Riddell, Hadden & Montgomery, 1978). Another possible explanation involves alterations in protein binding: if the fraction of catecholamines bound to plasma proteins was substantially reduced (and, conversely, the free fraction increased) then an apparent increase in sensitivity to catecholamines might be seen.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the clinical manifestations of this disease resemble the effects of stimulation of the sympathetic nervous system, but the reasons for this have never been satisfactorily explained. Increased sensitivity to catecholamines has been said to occur in hyperthyroidism, but catecholamine concentrationresponse curves have not been found to alter in patients when they were hyperthyroid compared to when they were euthyroid (Aoki, Wilson & Theilin, 1972;McDevitt, Riddell, Hadden & Montgomery, 1978). Another possible explanation involves alterations in protein binding: if the fraction of catecholamines bound to plasma proteins was substantially reduced (and, conversely, the free fraction increased) then an apparent increase in sensitivity to catecholamines might be seen.…”
Section: Resultsmentioning
confidence: 99%
“…However, this hypothesis has been questioned on the basis that plasma catecholamine levels are normal and even low in hyperthyroid patients [2][3][4]. In addition, controversial data have been obtained with respect to cardiovascular sensitivity to catecholamines [10,11] or to the number of fl-adrenergic receptors present in hyperthyroidism [12]. Similarly, the observation that fl-adrenoceptor blockade induces a reduction in heart rate of equivalent magnitude in normal and hyperthyroid conditions does not suggest an increase in sympathetic activity in human hyperthyroidism [13][14][15].…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies have suggested that an altered car¬ diovascular sensitivity to circulating catecholamines might exist in hyperthyroidism (Harrison 1964;Waldstein 1966) but more recent work has not confirmed this suggestion (Aoki et al 1967;Levey 1971;McDevitt et al 1978). The adenylate cyclase system is involved in the peripheral actions of catecholamines (Sutherland & Robison 1966;Broadus 1977) and following increased ß-adrener¬ gic stimulation plasma and urinary excretion of cAMP were raised (Ball et al 1972;Kunitada et al 1978).…”
mentioning
confidence: 87%